2022
DOI: 10.3390/aerospace9050261
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Tiltrotor Flow Field during Shipboard Take-Off and Landing Based on CFD-CSD Coupling

Abstract: Due to the small tilt angle, a tiltrotor operates in non-axial flow conditions during shipboard take-off and landing. The non-uniformity of the blade’s air-load is high, resulting in structural deformation with high fluctuation frequency, affecting the rotor’s aerodynamic characteristics. A new computational fluid-dynamic computational structural dynamics (CFD-CSD) solver is proposed to analyze the effects of the blade’s elastic deformation on the aerodynamic characteristics. This method is suitable for the ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The CFD analysis is based on the Unsteady Reynolds-Averaged Navier-Stokes (URANS) equations and the CSD analysis is constructed based on the Timoshenko beam model. The coupling method was used in a previous study [19] for the simulation of tiltrotor flow field during shipboard take-off and landing. By analyzing the results of soft in-plane and stiff in-plane tiltrotor blades in conversion flight, this study found that the influence of the difference in the structural characteristics of the blades on the aerodynamic force is quite different in the first and last halves of the tilting action, being more significant in the first half than in the last half.…”
Section: Introductionmentioning
confidence: 99%
“…The CFD analysis is based on the Unsteady Reynolds-Averaged Navier-Stokes (URANS) equations and the CSD analysis is constructed based on the Timoshenko beam model. The coupling method was used in a previous study [19] for the simulation of tiltrotor flow field during shipboard take-off and landing. By analyzing the results of soft in-plane and stiff in-plane tiltrotor blades in conversion flight, this study found that the influence of the difference in the structural characteristics of the blades on the aerodynamic force is quite different in the first and last halves of the tilting action, being more significant in the first half than in the last half.…”
Section: Introductionmentioning
confidence: 99%